PENGARUH STRATEGI PEMBELAJARAN RESUME KELOMPOK TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 1 PALEMBANG - Eka Putri Santi; M. Djahir Basir; Siti Fatimah (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2014)
The problem of this research is whether there is a difference of influence of learning strategy of group resume with learning strategy of two head power toward student learning outcomes on economic subjects in SMA Negeri 1 Palembang. The purpose of this research is to know the difference of influence of learning strategy of group resume with learning strategy of strength of two head to student learning outcomes at economic subject at SMA Negeri 1 Palembang Population in this research is all student of class X in SMA Negeri 1 Palembang school year 2012-2013 which consists of 12 classes and amounted to 369 students. The sample of this study is clustar random sampling, so that the class X.7 which is 31 students of experimental class given treatment in the form of group resume learning strategy, and class X.8 which amounted to 31 students as control class given treatment in the form a two-head force learning strategy. This research is a True Experimental Design research with posttest only design design. Data collection techniques used in this study is the test aims to measure student learning outcomes. Learning result data which have been obtained then analyzed by KKM of 75 sheets of observation aims to know the conformity of research implementation with lesson plan, and to know whether there is difference of influence of group resume learning strategy with strategy of learning force of two head used t test formula. After testing on the hypothesis can be concluded that there are differences in the effect of resume learning strategy with the influence of learning the strength of two heads towards the learners learn. From these studies, it is suggested for teachers to use group resume learning strategy as an alternative learning to be more able to improve learning outcomes of learners.